Cadenas cortas de comercialización como estrategia para la conservación de la agrobiodiversidad: el caso de la Agroferia Campesina del distrito de Magdalena del Mar - Aliaga Mayhuasca, Jacqueline Lizeth (2024)
This study examines the role of the Agroferia Campesina de Magdalena in promoting agrobiodiversity among small-scale agricultural producers in Lima, Peru. Employing a qualitative methodology encompassing interviews, participant observation, and document analysis, the research explores how this short food supply chain influences agricultural practices and the conservation of native species. The findings reveal that the Agroferia, which evolved from an externally driven project to a self-managed association, has created a space where farmers can directly market a diverse range of products, thereby incentivizing the conservation of traditional varieties and agroecological practices. Furthermore, it has fostered awareness among urban consumers about the importance of agrobiodiversity. However, the study identifies structural tensions, such as the precariousness of the legal framework and barriers in certification systems, which constrain the initiative's transformative potential. The research concludes that while Agroferias represent a promising model for linking agrobiodiversity conservation with sustainable rural development, they require enhanced political support and appropriate regulatory frameworks to maximize their impact and ensure their continuity.